Inequality, corruption, and competition in the presence of market imperfections - Indranil Dutta; Ajit Mishra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
We analyze the relation between inequality, corruption and competition in a developing economy context where markets are imperfect. We consider an economy where different types of households (efficient and inefficient) choose to undertake production activities. For production, households borrow capital from the credit market. They also incur non-input costs which they could avoid by bribing inspectors. Due to information asymmetry and wealth inequality, the credit market fails to screen out the inefficient types. In addition to the imperfect screening, the inefficient type's entry is further facilitated by corruption. We analyze the market equilibrium and look at some of the implications. We show that a rise in inequality can lead to an increase in corruption along with greater competition. – corruption ; competition ; credit market ; inequality ; screening
Keywords: D31; D43; K42; O12; 330; Einkommensverteilung; Korruption; Wettbewerb; Kreditmarkt; Unvollkommener Markt